Extensive cutaneous mucormycosis: a case report - Vásquez-Palomino, Alvaro (2022)
Mucormycosis is an opportunistic infection caused by a group of filamentous fungi belonging to the subphylum Mucormycotina. The clinical presentation is diverse including rhino-cerebral, pulmonary, cutaneous, gastrointestinal and disseminated locations. Cutaneous mucormycosis account for 19% of all cases. We report the case of a young male presenting with extensive cutaneous involvement after a burn with an unknown substance followed by local application of herbal medicines. He was initially treated in a peripheral health care center and was subsequently transferred to our hospital, where a surgical debridement was performed plus intravenous antimicrobial therapy with no improvement. A skin biopsy was performed showing fat necrosis and inflammation with granulocyte predominance. Broad hyphae were observed inside necrotic adipocytes characteristic of mucormycosis. The patient received parenteral antifungals plus surgical debridement but unfortunately died.